The interconnection between individual components of technical value and competitive results of the best aesthetic gymnastics groups in the world - Bulgacheva P.V.,; Novikova L.A. ,; Shugol E. А., (Theory and Practice of Physical Culture, 2024)
The purpose of the research is to determine the interconnection between technical and artistic value, execution of the competition programs and the final score of the best aesthetic gymnastic groups in the world. Research methods and procedure. Pedagogical observations were undertaken during the World Championship 2023 in Almaty. The study involved top six senior aesthetic gymnastics groups (three groups from Russia, two groups from Bulgaria and one from Japan). Research results and discussion. The maximum score in aesthetic gymnastics is 30 points, consisting of three components with the maximum of 10 points for each component. To determine the interconnection between the individual components and the competitive results, the rank correlation analysis was conducted, which allowed to identify the degree of influence of each component on the final score. According to the results of the conducted rank correlation analysis, we obtained rank correlation coefficients equal to 0,97; 0,70; 0,93 indicating strong and moderate association between the individual components of execution and competitive results. Conclusions. The correlation analysis revealed strong association between technical value and the competitive result r=0,97; between execution and the competitive result r=0,93; moderate association between artistic value and the competitive result r=0,70.